Viral genome-based Zika virus transmission dynamics in a paediatric cohort during the 2016 Nicaragua epidemic. - Sun, H; Binder, RA; Dickens, B; de Sessions, PF; Rabaa, MA; Ho, EXP; Cook, AR; Carrillo, FB; Monterrey, JC; Kuan, G; Balmaseda, A; Ooi, EE; et al. (Elsevier, 2021)
Background Nicaragua experienced a large Zika epidemic in 2016, with up to 50% of the population in Managua infected. With the domesticated Aedes aegypti mosquito as its vector, it is widely assumed that Zika virus transmission occurs within the household and/or via human mobility. We investigated these assumptions by using viral genomes to trace Zika transmission spatially. Methods We analysed serum samples from 119 paediatric Zika cases participating in the long-standing Paediatric Dengue Cohort Study in Managua, which was expanded to include Zika in 2015. An optimal spanning directed tree was constructed by minimizing the differences in viral sequence diversity composition between patient nodes, where low-frequency variants were used to increase the resolution of the inferred Zika outbreak dynamics. Findings Out of the 18 houses where pairwise difference in sample collection dates among all the household members was within 30 days, we only found two where viruses from individuals within the same household were up to 10th-most closely linked to each other genetically. We also identified a substantial number of transmission events involving long geographical distances (n=30), as well as potential super-spreading events in the estimated transmission tree. Interpretation Our finding highlights that community transmission, often involving long geographical distances, played a much more important role in epidemic spread than within-household transmission. Funding This study was supported by an NUS startup grant (OMS) and grants R01 AI099631 (AB), P01 AI106695 (EH), P01 AI106695-03S1 (FB), and U19 AI118610 (EH) from the US National Institutes of Health.